Design of environmental detector system application aims to promote awareness of pollution on campus - Amelia, Afritha; Roslina, Roslina; Sundawa, Bakti Viyata; Azis, Abdul; Pribadi, Banu Afwan (Bulletin of Electrical Engineering and Informatics, 2025)
Politeknik Negeri Medan (POLMED) was involved in the UI GreenMetric world rankings. The UI GreenMetric committee assessed green campus activities and environmental sustainability. The UI GreenMetric aims to raise awareness about sustainable campus greening, and social impacts of these endeavors. Based on the concept, an environmental detection system (EDS) was developed using internet of things (IoT) technology. The EDS can detect and monitor environmental parameters remotely such as carbon dioxide (CO2), noise levels, light intensity, air temperature, relative humidity, and dust particle density in real-time via the internet. Measurements of environmental parameters were conducted at one location in POLMED. The average CO2 level was 485 ppm. The average noise level was 53.40 dB. The average light intensity was 129 lux. The average air temperature was 26.60 °C. The average of relative humidity was 63.8% RH. The average of PM2.5 dust particle densities was 23 µg/m3. The average of PM10 dust particle densities was 29 µg/m3. Based on these results, the air quality has begun to be polluted because this value is already above the threshold clean quality air set by the Government of the Republic of Indonesia (310–330 ppm).